Unraveling the impact of phytoplankton secretions on the behavior of metal-containing engineered nanoparticles in aquatic environment - Gasco, Rocco; Slaveykova, Vera I. (Frontiers in Environmental Science, 2024)
Based on the up-to-date knowledge we critically discuss the current understanding of the influence of the compounds secreted by phytoplankton species on the fate of metal-containing engineered nanoparticles (ENPs) in aquatic settings. Different biomolecules, such as extracellular polymeric substances (EPS) and exometabolites play important, yet to elucidate, role in the dissolution, colloidal stability, transformations and biouptake of the ENPs and thus shape their behavior within the phycosphere. Phytoplankton secretions can also mediate the synthesis of ENPs from dissolved ions by reducing the metals ions and capping the newly formed ENPs. However, the environmental significance of this process remains to be demonstrated. Exposure to ENPs triggers changes in the secretion of the biomolecules. An improved understanding the regulatory mechanism and exometabolite changes due to ENP exposure is essential for deciphering the ENPs-phytoplankton interactions. Unveiling the significance of secreted biomolecules in modulating the behavior of the metal-containing ENPs is central for understudying the phytoplankton-ENPs feedbacks, drivers of transformations of ENPs and their mechanisms in the aquatic environment.